Intensity of physical therapy services: Association with work and health outcomes in injured workers with back pain in Washington State. Issue 1 (12th November 2022) - Chin, Brian; Rundell, Sean D.; Sears, Jeanne M.; Fulton‐Kehoe, Deborah; Spector, June T.; Franklin, Gary M.
Abstract: Background: Associations between the intensity of physical therapy (PT) treatments and health outcomes among individuals with back pain have been examined in the general population; however, few studies have explored these associations in injured workers. Our study objective was to examine whether intensity of PT treatments is positively associated with work and health outcomes in injured workers with back pain. Methods: We conducted a secondary analysis of prospective data collected from the Washington State Workers' Compensation (WC) Disability Risk Identification Study Cohort (D‐RISC). D‐RISC combined survey results with WC data from the Washington State Department of Labor and Industries. Workers with a State Fund WC claim for back injuries between June 2002 and April 2004 and who received PT services within the first year of injury were eligible. Intensity of PT treatment was measured as the type and amount of PT services within 28 days from the first PT visit. Outcome measures included work disability and self‐reported measures for working for pay, pain intensity, and functional status at 1‐year follow‐up. We conducted linear and logistic regression models to test associations. Results: We identified 662 eligible workers. In adjusted models, although the intensity of PT treatment was not significantly associated with work disability at 1‐year follow‐up, it was associated with lower odds of working for pay, decreased pain intensity, and improved functional status. Conclusions: Our findings suggest that there may be small benefits from receiving active PT, manual therapy, and frequent PT treatments within 28 days of initiating PT care.